Inventarisasi Makanan Khas Tana Luwu Sebagai Bentuk Perlindungan Hukum Indikasi Geografis - Fitriani Jamaluddin; Muhammad Ashabul Kahfi; Fitriah Faisal (Al-Adl : Jurnal Hukum, 2022)
The purpose of this study is to take an inventory of Tana Luwu's special food, the factors that cause the absence of Tana Luwu's special food that is registered with geographical indications and to describe the efforts that can be made by the Local Government in Tana Luwu in providing protection for Geographical Indications of Tana Luwu's Products. The method used in this research is empirical research. The informants in this study are food businesses in Tana Luwu and the government from the Cooperatives and MSME service in Tana Luwu. Research data was obtained by conducting observations, interviews, and documentation and then processed qualitatively. In Tana Luwu, there are no special foods that receive geographic indication protection, due to several factors, including the absence of data related to typical foods in the Tana Luwu area, and the lack of socialization related to the importance of legal protection of geographical indications for typical foods. Cooperation is needed between the Government, typical food entrepreneurs, and academics in providing legal protection for geographical indications for typical foods in the Tana Luwu area.